Analysis of apoptosis of kidney tissue by the tunel method and histomorphological changes in rabbit kidney model due to unilateral supravesical obstruction - Uçak, Ramazan; Topçu, Şükrü Oğuzkan; Sarı, İbrahim (Journal of Surgery and Medicine, 2020)
Aim: There is a need for effective, cheap, and fast method to detect apoptosis. In some studies, we see that newer, more difficult, expensive, or less effective methods are used. We wanted to show that the TUNEL method has serious advantages and can still be used alone. In this study, it was aimed to investigate whether there is a significant difference in the number of apoptotic cells in partial obstruction (PO) and complete obstruction (CO) by using terminal deoxytransferase-mediated bio-dUTP nick and labeling (TUNEL) method in renal tissue. We also evaluated histopathological changes after renal obstruction. Methods: In this study, 29 rabbits were used. Supravesical obstruction was created in 24 rabbits. Five rabbits were used as the control group. Twelve kidneys were examined after creating unilateral partial obstruction and 12, after the creation of unilateral complete obstruction. Histomorphological changes in kidney tissues in routine Haemetoxylene-Eosine (HE) preparations and apoptosis in preparations obtained by TUNEL method were examined. Results: Apoptotic cells were observed especially in the tubules by the TUNEL method. The average number of apoptotic cells in CO and PO groups were 190.66 and 40.58, respectively. In the CO group, the number of apoptotic cells was significantly higher than that in the PO group (P<0.001). Interstitial fibrosis, chronic inflammatory infiltration, tubular destruction (vacuolar changes, cystic and atrophic tubules) were observed in both groups. These changes were more limited, and mild, in the PO group, and severe and widespread in the CO group. Conclusion: TUNEL method is one of the highly effective methods in detecting apoptosis. It was observed that apoptosis and pathological changes developing in the kidney tissue after complete obstruction were more severe and widespread.